2023
DOI: 10.3390/molecules28083352
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro: The Effects of the Anticoccidial Activities of Calotropis procera Leaf Extracts on Eimeria stiedae Oocysts Isolated from Rabbits

Abstract: Hepatic coccidiosis is an infectious and mortal disease that causes global economic losses in rabbits. The research aimed to assess the efficacy of Calotropis procure leaf extracts on the inhibition of Eimeria stiedae oocysts and to determine the optimal dosage for suppressing the parasite’s infective phase. In this experiment, oocyst samples per milliliter were tested, and 6-well plates (2 mL) of 2.5% potassium dichromate solution containing 102 non-sporulated oocysts on Calotropis procera leaf extracts were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Our findings are better than those reported for pulp and leaf olive extracts (25.36% and 5.87%, respectively) [22,60], whereas 60.53 ± 0.38 mg/mL of OFI peel extract destroyed 50 oocysts (Figure 5), which is higher than the reported values of Debbou-Iouknane, Nerín, Amrane-Abider, and Ayad [22], where 192.94 mg/mL of olive leaves destroyed half of the Eimeria oocysts isolated from broiler chickens. Moreover, while the present results were better even against Eimiria isolated from other animals like rabbits, Murshed et al [61] revealed that the oocyst inhibition percentages were low (below 50%) using 25-100 mg/mL of Calotropis procera leaf.…”
Section: Anticoccidial Activitiesmentioning
confidence: 46%
“…Our findings are better than those reported for pulp and leaf olive extracts (25.36% and 5.87%, respectively) [22,60], whereas 60.53 ± 0.38 mg/mL of OFI peel extract destroyed 50 oocysts (Figure 5), which is higher than the reported values of Debbou-Iouknane, Nerín, Amrane-Abider, and Ayad [22], where 192.94 mg/mL of olive leaves destroyed half of the Eimeria oocysts isolated from broiler chickens. Moreover, while the present results were better even against Eimiria isolated from other animals like rabbits, Murshed et al [61] revealed that the oocyst inhibition percentages were low (below 50%) using 25-100 mg/mL of Calotropis procera leaf.…”
Section: Anticoccidial Activitiesmentioning
confidence: 46%